Estudo de formação de tris-acetal internoe espiro-carbocíclicos a partir de (R)-(–)-e espiro-carbocíclicos a partir de (R)-(–) - Desiderá, André Luiz (Universidade Federal de São Carlos, 2016)
In this work we studied, initially, the formation of the internal tris-ketals derivatives from their respective 2,2-bis-propargyl cyclic ketones from catalysis by gold complexes. The reaction conditions were studied for synthesis of this class of compounds, variations of catalysts with and without addition of co-catalysts, the substituents effect on propargylic carbon, theoretical calculation of the thermodynamic stability of the keto x acetal form and theoretical calculation of chemical shift versus the empirical results for structural confirmation. Based on these results and published reports, mechanisms have been proposed to explain the formation of the obtained products. In a second stage of this work, we studied the diastereoselective 2,2-bisallylation of cicloeptenona and further formation of spiro [6.4] bicyclo system from the ring closure metathesis reaction (RCM). The scope of this work was prepared from 2,2-bis-allyl-cycloalkanones and subsequent RCM using 5 different ruthenium catalysts, varying the solvent and reaction temperature.
Study of formation of internal tris-ketals and spiro-carbocyclics e espiro-carbocíclicos a partir de (R)-(–)
Keywords: Tris-acetal interno; Espiro-carbocíclicos; Carvona; Tris-ketals derivates; Espiro-carbociclicos; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA